Quality and high yield synthesis of Ag nanowires by microwave-assisted hydrothermal method - Meléndrez, Manuel F.; Medina de la Garza, Carlos Eduardo; Solís Pomar, Francisco; Flores, Paulo; Paulraj, Mani; Pérez Tijerina, Eduardo (Springer, 2015)
Silver nanowires (Ag-NWs) were obtained using microwave-assisted hydrothermal method (MAH). The main advantage of the method is its high NWs production which is greater than 90%. It is also easy, fast, and highly reproducible process. One of the drawbacks presented so far in the synthesis of nanostructures by polyol path is the high temperature used in the process, which is superior than the boiling point of solvent (ethylene glycol), and also its excessive reaction time. Here, Ag-NWs with diameters of 70 to 110 nm were synthesized in 5 min in large quantities. Results showed that dimensions and shape of nanowires were very susceptible to changes with reaction parameters. The reactor power and reactor fill capacity were important for the synthesis. It was found that the reaction time needs to be decreased because of the NWs which start to deform and break up due to significant increase in the pressure's system. Energy-dispersive X-ray spectroscopy and electron diffraction analysis (SAED) did not show corresponding phases of AgO. Some aspects about synthesis parameters which are related to the percent yield and size of nanowires are also discussed.